2014
DOI: 10.1111/jmwh.12187
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Maternity Care Providers in Promoting Shared Decision Making Regarding Birthing Positions During the Second Stage of Labor

Abstract: Introduction Through the use of a variety of birthing positions during second stage labor, a woman can increase progress, improve outcomes, and have a positive birth experience. The role maternity care providers play in determining which position a woman uses during second stage has not been thoroughly explored. The purpose of this qualitative investigation was to explore how maternity care providers communicate with women during second stage labor regarding birthing position. Methods A literature informed f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 47 publications
1
19
0
5
Order By: Relevance
“…Our findings reinforce the perception that decision‐making in maternity care is a complicated, multifaceted experience with potential for improvement . We found that a large majority of mothers reported having a discussion with their maternity care providers about how to give birth after 1 or 2 prior cesareans, and about half reported a discussion about spontaneous vs induced labor after being told their baby might be quite large.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings reinforce the perception that decision‐making in maternity care is a complicated, multifaceted experience with potential for improvement . We found that a large majority of mothers reported having a discussion with their maternity care providers about how to give birth after 1 or 2 prior cesareans, and about half reported a discussion about spontaneous vs induced labor after being told their baby might be quite large.…”
Section: Discussionsupporting
confidence: 83%
“…Corresponding items in the participation domain in the original CEQ assessed possibilities to be up and free to move, and to select birthing position and pain relief. Women's choices of mobility and upright positions [43] during labour are beneficial, and should be encouraged [44]. Whilst one newly developed item addressing mobility did not fit in the yielded model, and was thus excluded in the CEQ2, new items relating to receiving information and involvement in decision-making were identified to be of greatest importance and relevance to include [45].…”
Section: Discussionmentioning
confidence: 99%
“…Dieser könnte aber laut Autorenteam auch an einer verbesserten Messung des Blutverlustes liegen. Abgesehen von den körperlichen Auswirkungen haben Frauen, die aufrecht gebären oder ihre Position selbst aussuchen, ein stärkeres Kontrollgefühl und ein besseres Geburtserleben [21] [23]. Dieser letzte Punkt kann gerade im Hinblick auf die Prävention traumatisierender Geburtshilfe einen hohen Stellenwert einnehmen.…”
Section: Das Cochrane Review Von Gupta Et Al Betrachtet Dieunclassified
“…Wenn während der Geburt Komplikationen auftreten (z. B. Schulterdystokie oder abnormale fetale Herzfrequenz), wird auch die Position der Gebärenden verändert [21] [10]. Leider wird das nur erwähnt und nicht näher beschrieben, welche Positionen ausgewählt werden.…”
Section: Geburtshilfliche Faktorenunclassified
See 1 more Smart Citation